Cryptosporidiosis among birds and bird handlers at Zoo Negara, Malaysia - Lim, Yvonne Ai Lian; Rohela, M.; Shukri, M.M. (SEAMEO Regional Tropical Medicine and Public Health Network, 2007)
This study was carried out at the Malaysian National Zoo to ascertain, not only the current prevalence rate in the birds, but also to determine the association between cryptosporidiosis in birds and the bird handlers. A total of 116 fecal samples from 71 species of birds were collected from six different locations in Zoo Negara, and eight fecal samples from bird handlers were also sampled. Results showed that the prevalence of Cryptosporidium oocysts in birds and bird handlers were 3.4 and 12.5, respectively. The birds that were positive for cryptosporidiosis were Wreathed Hornbill (Aceros undulatus) and Great Currasow (Crax rubra) from the aviary, Bushy-crested Hornbill (Anorrhinus galeritus) from the bird house, and the Common Peafowl (Pavo cristatus) from the lake. Birds at the lake showed the highest percentage (12.5) of positivity, followed by birds at the aviary (5.4) and the birdhouse (2.8). Result of the present study seemed to indicate that cryptosporidiosis might be spreading to other species of birds and to other locations in the zoo, which was not previously documented. This study also suggested the probable association of cryptosporidiosis among birds and their bird handlers. However, conclusions can only be drawn after the confirmation of speciation found in birds and bird handlers through molecular identification.